Effect of Ionic Liquid Pretreatment On the Moisture Absorption Kinetics of Oil Palm Biomass Based Composites - Jugindar Singh, Ashwin Pal Singh (Universiti Teknologi PETRONAS, 2016)
Pre-treatment of oil palm fiber using ionic liquids have been identified as a very green and environmentally friendly method. This research objective is to study the effect of ionic liquid pretreatment on the moisture absorption kinetics of oil palm biomass based composites. Oil palm fronds (OPF) fibers were pre-treated using IL [Bmim][Cl], pretreated using IL [Emim][DEP] and one part left untreated. All the samples were then fabricated into biocomposite boards using binder made out of corn starch and glycerol. All 3 types of biocomposite board then underwent study of water kinetics. The relative humidity (RH) was manipulated to study the effects on the water absorption of the bio composite boards. The water uptake percentage at equilibrium for 33% RH is highest for the untreated board at 5.12% compared to [BMIM][Cl] at 3.59% and [EMIM][DEP] at 3.45%. The water uptake percentage at equilibrium for 75% RH is highest for the untreated board at 8.66% water absorbed compared to [BMIM][Cl] at 5.80% and [EMIM][DEP] at 7.91%. The water uptake percentage at equilibrium for 100% RH is highest for the untreated board at 123.39% water absorbed compared to [BMIM][Cl] at 88.43% and [EMIM][DEP] at 102.04%.